Development of autotaxin inhibitors: A series of tetrazole cinnamides. (1st January 2021) - Thomson, Christopher G.; Le Grand, Darren; Dowling, Mark; Beattie, David; Elphick, Lucy; Faller, Michael; Freeman, Mark; Hardaker, Elizabeth; Head, Victoria; Hemmig, Rene; Hill, Johan; Lister, Andrew; et al.
Abstract: A series of inhibitors of Autotaxin (ATX) have been developed from a high throughput screening hit, 1a, which shows an alternative binding mode to known catalytic site inhibitors. Selectivity over the hERG channel and microsomal clearance were dependent on the lipophilicity of the compounds, and this was optimised by reduction of clogD whilst maintaining high affinity ATX inhibition. Compound 15a shows good oral exposure, and concentration dependent inhibition of formation of LPA in vivo, as shown in pharmacokinetic-pharmacodynamic (PK/PD) experiments.